Circulating Concentrations of Essential Fatty Acids, Linoleic and α-Linolenic Acid, in US Adults in 2003–2004 and 2011–2012 and the Relation with Risk Factors for Cardiometabolic Disease: An NHANES Analysis. Issue 10 (28th September 2020) - Petersen, Kristina S; Sullivan, Valerie K; Fulgoni, Victor L; Eren, Fulya; Cassens, Martha E; Bunczek, Michael T; Kris-Etherton, Penny M
ABSTRACT: Background: The increased use of high-oleic oils to replace trans fat has led to concern about declining intake of PUFA and the potential for essential fatty acid insufficiency or even deficiency. Objectives: The aim of this study was to examine circulating concentrations of essential and poorly biosynthesized fatty acids, as biomarkers of dietary intake, in the NHANES data sets prior to (2003–2004 cycle) and following (2011–2012 cycle) legislation to reduce trans fat in the food supply and also to explore the associations between these fatty acids and markers of cardiometabolic health. Methods: Fasting circulating concentrations of fatty acids from adults (aged ≥20 y) in the 2003–2004 and 2011–2012 NHANES cycles were used for analysis. Dietary data from one day of both the 2003–2004 and 2011–2012 cycles were used to examine differences in dietary fatty acid intake between these cycles. Regression analyses were used to assess relations between circulating concentrations of fatty acids and cardiometabolic health. Results: Between the 2003–2004 and 2011–2012 NHANES cycles, LA dietary intake increased (1.38 g, P = 0.002); no difference in circulating concentrations was observed. ALA, measured by dietary intake (0.23 g, P < 0.01) and circulating concentrations (0.14%, P < 0.001), increased from 2003–2004 to 2011–2012. Circulating LA was inversely associated with BMI (in kg/m 2 ; regression coefficient per percentage point change in LA ± SE: –0.22 ± 0.04), waist circumference (–0.62 ± 0.09 cm), systolic blood pressure (–0.38 ± 0.09 mm Hg), triglycerides (–9.92 ± 0.63 mg/dL), glucose (–3.34 ± 0.13 mg/dL), insulin (–0.18 ± 0.05 µU/mL), and HOMA-IR (–0.29 ± 0.05). Conclusions: In a nationally representative sample of US adults, no declines in circulating concentrations of essential fatty acids, LA and ALA, were observed between 2003–2004 and 2011–2012, a time when high-oleic oils were increasingly used in the food supply. Higher amounts of circulating LA were correlated with lower risk of cardiometabolic dysfunction, which underscores the importance of monitoring consumption in the United States.